Monodopsis and Vischeria Genomes Shed New Light on the Biology of Eustigmatophyte Algae. (19th October 2021) - Yang, Hsiao-Pei; Wenzel, Marius; Hauser, Duncan A; Nelson, Jessica M; Xu, Xia; Eliáš, Marek; Li, Fay-Wei
Abstract: Members of eustigmatophyte algae, especially Nannochloropsis and Microchloropsis, have been tapped for biofuel production owing to their exceptionally high lipid content. Although extensive genomic, transcriptomic, and synthetic biology toolkits have been made available for Nannochloropsis and Microchloropsis, very little is known about other eustigmatophytes. Here we present three near-chromosomal and gapless genome assemblies of Monodopsis strains C73 and C141 (60 Mb) and Vischeria strain C74 (106 Mb), which are the sister groups to Nannochloropsis and Microchloropsis in the order Eustigmatales. These genomes contain unusually high percentages of simple repeats, ranging from 12% to 21% of the total assembly size. Unlike Nannochloropsis and Microchloropsis, long interspersed nuclear element repeats are abundant in Monodopsis and Vischeria and might constitute the centromeric regions. We found that both mevalonate and nonmevalonate pathways for terpenoid biosynthesis are present in Monodopsis and Vischeria, which is different from Nannochloropsis and Microchloropsis that have only the latter. Our analysis further revealed extensive spliced leader trans -splicing in Monodopsis and Vischeria at 36–61% of genes. Altogether, the high-quality genomes of Monodopsis and Vischeria not only serve as the much-needed outgroups to advance Nannochloropsis and Microchloropsis research, but also shed new light on the biology and evolution of eustigmatophyte algae.